Paternalistic approach towards the Orang Asli in Malaysia: tracing its origin and justifications - Rohaida Nordin,; Witbrodt, Matthew Albert; Muhamad Sayuti Hassan@Yahya, (School of Social, Development and Environmental Studies, Faculty of Social Science and Humanities, Universiti Kebangsaan Malaysia, 2016)
Issue and challenges pertaining to land and the native communities loom large in contemporary Malaysian political and economic affairs. Responding to them often necessitates an understanding of their genesis. The main objective of this study was to examine the importance of land and natural resources to the life of the Orang Asli, and to demonstrate that their limited autonomy was the reason why the British claimed that they needed state protection. To achieve this objective secondary data were examined to provide information background of the Orang Asli, the relationship between Orang Asli and the Malays during pre-colonial period, the relationship between the Orang Asli and the British colonial government during colonial periods, and the relevant policies towards the Orang Asli by both the Malays and the British colonial government during the pre-colonial and colonial periods. This article concludes that the paternalistic approach towards the Orang Asli was adopted during the pre-colonial period and the approach was continued and to the certain extent worsened during British colonial period in which the Orang Asli were treated in a paternalistic manner as compared to the Malays, in particular, with regard to land matters.